CUSTOMER SATISFACTION MEDIATES E-SERVICE QUALITY TOWARDS USER LOYALTY IN MOBILE JKN USERS - Tria Monika Dewi; Hery Winoto TJ; Melitina Tecoalu (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
Universal Health Coverage (UHC) means everyone has access to the qualityfiedhealthcare anytime and anywhere they need it, without financesproblems. In order to realize UHC, the Indonesian Government has implemented the National Health Insurance program (JKN/KIS) which is organized by BPJS Health. Along with increasingly rapid technological developments, BPJS Health is implementing health innovationcalledMobile JKN. Therefore, it is necessary to evaluate whether the public feels satisfied and loyal to theservicequality from the health application. The research sample was taken from 105 respondents who had used the Mobile JKN application at RS P Cirebon more than once and were >18 years old. Data was obtained through a random questionnaire via Google Form. Questionnaire data was processed using the Microsoft Excel application and analyzed using SEM-PLS (Structural Equation Modeling-Partial Least Square) and SmartPLS version 4 application. The research results show that e-service quality has a significant positive effect on customer satisfaction and user loyalty of Mobile JKN with p-values ​​of 0.000 and 0.0005 respectively. Customer satisfaction has a significant positive effect on user loyalty of Mobile JKN users (p-value 0.000), and e-service quality has a significant positive effect on user loyalty mediated by customer satisfaction of Mobile JKN users (p-value 0.000). These results are in line withprevious studies. We hopethat Mobile JKN application managers can continue to improve e-service quality so that they can make a positive and significant contribution both directly and indirectly to customer satisfaction and user loyalty, and expand the collaboration network with various health facilities.